The Future of Physiology: Cardiac Electrophysiology - Coronel, R. (Frontiers in Physiology, 2020)
Is cardiac electrophysiology complete? What are the challenges that are to be met in cardiac electrophysiology and how can we best engage these? These questions will be addressed in view of the progressing subspecialization of the field. A suggested answer lies in multidisciplinary and extradisciplinary approaches.